Learning How To Refine And Cast Copper - A Page From The History Of Development Of Electrolytic Refining And Mechanical Casting - Arthur L. Walker (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
In June, 1893, while I was with the Old Dominion Copper Co. at Globe, Ariz., I received an offer to take charge, as manager, of the Baltimore Electric? Refining Co. which had recently built a plant at Baltimore, Md., having a capacity of about 1200 tons of electrolytic copper per month, using the Hayden series system. This was a very large output, for in those days the plants were small and the art was in its infancy. At the beginning of 1893 there were 11 electrolytic refineries in the United States, most of them using the multiple system. The Hayden series system was used at Baltimore and Bridgeport and the Smith series system was in operation at the Electrolytic Copper Co. at Ansonia, COM., and at the Pennsylvania Salt Co. at Philadelphia. In the latter system the plates were placed in a horizontal position, but the operating difficulties were so numerous it was soon discarded. The total production of these 11 plants in 1892 was very small; I have not been able to discover reliable figures of production. There were about thirty electrolytic copper refineries in the world that year, according to Titus Ulke, and the entire production of these